THE MANAGEMENT OF SOLID WASTE, LIQUID WASTE AND NOXIOUS SYNANTHOPIC FAUNA IN THE HARBOR FORTRESS - Oliveira, Ivan de; Menezes, Maria Oziléa Bezerra; Maia, Luis Parente (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The article aims to diagnose the port environmental management of the Port of Fortaleza, chart its profile and propose improvement actions for the management of solid waste, liquid waste and noxious synanthropic fauna. Data were collected from port authorities, stakeholders authorities and tenants. A mapping of the Port of Fortaleza was performed, and then the questionnaires and collection of primary data (in situ) by students and faculty of the Institute of Marine Sciences - LABOMAR, Federal University of Ceará. The research identified the urgent need for a Management Plan established between the port authority, intervening authorities and tenants in the sense that the solid wastes, liquid effluents and noxious synanthropic fauna observed at the Port of Fortaleza are properly minimized allowing thus, safer management.